Patrones de distribución de las especies de Cynanchum, Diplolepis y Tweedia (Apocynaceae: Asclepiadoideae) de América del Sur austral - Hechem, Viviana; Acheritobehere, Laura; Morrone, Juan J. (Revista de Geografía Norte Grande, 2021)
The individual tracks of 13 species and one variety of Cynanchum, Diplolepis, and Tweedia from austral South America (Argentina and Chile) were delineated, and based on their superposition five generalized tracks were identified: (1) northern Chile, supported by Cynanchum atacamense and Diplolepis boerhaviifolia; (2) north-central Chile, supported by Diplolepis geminiflora and D. menziesii; (3) central-south Chile, supported by Cynanchum myrtifolium and C. pachyphyllum; (4) central Chile and northern Argentinean Patagonia, supported by Cynanchum chilense, C. diemii, Diplolepis nummularifolia var. biflora, D. descolei, and D. nummuralifolia; and (5) western Argentina, supported by Tweedia australis, Diplolepis hieronymi, and Cynanchum bulligerum. Three nodes were found: (A) northern Chile (Coquimbo); (B) central Chile (Santiago); and (C) southern Argentina (southern Río Negro). The generalized tracks corroborate the relationship between the subregions of the Andean region and the South American Transition Zone. The nodes show possible zones of biotic contact that are evidence of the complex relationships of the austral biota. Finally, the relevance of this analysis for a Chilean Biogeographic Atlas is highlighted